Generation of an induced pluripotent stem cell (iPSC) line (BBANTWi009-A) from a Meester-Loeys syndrome patient carrying a BGN mutation - Pauline De Kinderen; Laura Rabaut; Anne Hebert; Peter Ponsaerts; Melanie Perik; Josephina A.N. Meester (Stem Cell Research, 2023)
Meester-Loeys syndrome (MRLS) is an X-linked syndromic form of thoracic aortic aneurysm and dissection. Here, we report an iPSC line (BBANTWi009-A) of a boy carrying a hemizygous BGN mutation (chrX:153502980-153530518del, GRCh38) causing MRLS. iPSCs were generated from dermal fibroblasts by reprogramming with the Cytotune®-iPS 2.0 Sendai Reprogramming Kit (Invitrogen). The generated iPSCs showed a normal karyotype, expressed pluripotency markers, were differentiated into the three germ layers and carried the original genotype.